DIALOG KARYA SEBAGAI STRATEGI KOMUNIKASI PENYELESAIAN KONFLIK BERMOTIF AGAMA TERHADAP MASYARAKAT ETNIS ROHINGNYA DI MYANMAR - Pohan, Syafruddin; Naku, Robertus Kristianto (CV. Kalimasada Group, 2023)
Phenomenal problems that have hit Myanmar have recently been in the spotlight of the mass media. The existence of a group of Buddhist extremists who commit violence against adherents of other religions gives its own color. Discrimination based on ethnic conflict between the majority and minorities is not only identified by religious elements, but also accompanied by political, social, cultural and economic elements. Government instability also supports the spread of this increasingly prolonged conflict. In fact, the existence and teachings of the Buddha on nibbana are also questionable. Nibbana is the ultimate reality, which is said to be a situation or condition where humans experience peace and emptiness when faced with the reality of violence that causes suffering, especially for Rohingya Muslims. The theological approach that can be offered in resolving such conflicts is comparative theology which boils down to dialogue of works. However, before reaching this stage, a theological disposition is needed by returning to their respective originality, strengthening their identity roots first and then establishing dialogue and cooperation with those who differ in comfort, openness, and harmony. Kata kunci: Konflik etnis, etnis Rohingnya, nibbana, dialog karya, orisinalitas, identitas, teologis.